EFEKTIFITAS WORD OF MOUTH TERHADAP MINAT BELI KONSUMEN PRODUK JIGAR FRUIT SALAD DI PLAZA SEMANGGI - Suhendra Suhendra (Jurnal Visi Komunikasi, 2015)
There are many ways to convey the message to promote, so that the target market right on target. To promote the growing consumer interest in buying that nominal required no small amount of good to advertise in print media, TV, internet, radio. This probably would not have happened if it can maximize the promotion by using the Word Of Mouth. It is applied by Jigar Fruit Salad which is a culinary business. Varian products include Mayo Fruit Salad, Yogurt Fruit Salad, Pickled Fruit Salad, Fruit Salad Rojak Caramel, honey Dazzling Fruit Salad, Fruit Rojak Serut Salad, Fruit Salad and Mango Fruit Toast. Jigar Fruit Salad has a target market aged 19-40 years, male and female students and employees, SES B, a healthy lifestyle. Jigar Fruit Salad is located in Plaza Semanggi Mall foodcourt with minimal skills possessed to start the promotion, Fruit Salad Jigar select Word of Mouth as a way to intensify the promotion, establish a commercially viable product and consumption with positioning as a healthy food and fresh as the most basis for intensifying Word of Mouth to reach consumers to buy the product Jigar fruit salad. Ada banyak cara untuk menyampaikan pesan untuk berpromosi, agar target market tepat sasaran. Untuk berpromosi sehingga minat beli konsumen tumbuh dibutuhkan nominal yang tidak sedikit untuk mengiklankan baik di media cetak, TV, internet, radio. Hal ini mungkin tidak akan terjadi jika dapat memaksimalkan promosi dengan menggunakan Word Of Mouth. Hal tersebut diaplikasikan oleh Jigar Fruit Salad yang merupakan satu bisnis kuline. Varian produknya antara lain Fruit Salad Mayo, Fruit Salad Yogurt, Fruit Salad Asinan, Fruit Salad Rujak Caramel, Fruit Salad honey Dazzling, Fruit Salad Rujak Serut, Fruit Manggo Salad dan Roti Panggang Buah.Jigar Fruit Salad mempunyai target market umur 19 – 40 tahun, laki- laki dan perempuan mahasiswa dan karyawan, SES B , bergaya hidup sehat. Jigar Fruit Salad terletak di Foodcourt Mall Plaza Semanggi dengan kemampuan minim yang dimiliki untuk memulai promosi, Jigar Fruit Salad memilih Word of Mouth sebagai salah satu cara untuk menggencarkan promosi, membentuk produk yang layak jual dan konsumsi dengan positioning sebagai makanan sehat dan segar sebagai kebutuhan paling dasar untuk menggencarkan Word of Mouth untuk menggapai minat beli konsumen terhadap produk Jigar fruit salad .